First megafloristic record for the Chubut Group at Somuncurá Canadón Asfalto Basin: An angiosperm dominated flora from the Upper Cretaceous Puesto Manuel Arce Formation, Patagonia Argentina - Passalia, Mauro Gabriel (2015)
The first association of fossil plantimpressionsin the Chubut Group at the Somuncurá-Cañadón Asfalto Basin is described herein. Themid-Cretaceous megafloral assemblage from Patagonia, Argentina was recovered from the Puesto Manuel Arce Formation.The taphocenosis consists mostly of leaves preserved as impressions, although a variety of cuticle remains are also present. Angiosperms are both quantitatively and qualitativelythe main component of the flora (at least 9 leaf morphotypes recognized). A few ferns and conifers complete the plant assemblage.The angiosperm leaves exhibit physiognomic heterogeneity with a variety of well-defined venation patterns.The myrtophyll morphotype (Myrtoidea sp.) and palmatilobed palinactinodromous leaves (Bamfordphyllum crassivena gen. et sp. nov.) are significant components of the assemblage. Flora characters are consistent with the Cenomanian - earliest Turonianage proposed for the Puesto Manuel Arce Formation. Comparisons were made with coeval Patagonian and extra-regional floras which suggest both local as well as long-distance gondwanan links.